Penerapan Media Film Animasi dalam Meningkatkan Kemampuan Agama Anak Usia 5-6 Tahun di RA Al-Barkah Medan Helvetia - Harahap, Salamiyah Nur Hakim; Khadijah, Khadijah; Daulay, Sholihatul Hamidah (Asian Journal of Early Childhood and Elementary Education, 2024)
This research was conducted at RA.Al-Barkah Medan Helvetia, Medan City, where initially during the pre-cycle phase, researchers observed a lack of religious knowledge among 5-6 year-old children at RA. Al-Barkah. This was attributed to the limited use of media in learning. Therefore, the researchers initiated a study titled "The Implementation of Animated Film Media in Enhancing the Religious Knowledge of 5-6 Year-Old Children at RA. Al-Barkah Medan Helvetia." The research questions were summarized into three points: assessing the children's religious knowledge before watching animated films, examining the implementation process of animated films in enhancing the religious knowledge of children aged 5-6 years at RA. Al-Barkah, and evaluating whether the children's religious knowledge improved after watching these animated films. The research design adopted was Classroom Action Research, consisting of four cyclic stages: (1) Planning, (2) Implementation, (3) Observation, and (4) Reflection. The researcher prepared instruments to facilitate the observation of the children's religious knowledge. The results of the study, involving 20 participants, showed that 2 children (10%) were categorized as Developing Very Well (DVW), 14 children (70%) as Developing As Expected (DAE), 4 children (20%) as Starting to Develop (STD), and none were categorized as Not Developing Yet (NDY). The steps taken to increase a child's religious abilities are: Opening activities, core activities, and closing activities. Active guidance is provided during the core activities, and recognition is given during the closing activities.